The terrain features of the Surdash fold - Ali Taher, Marwa; AL-Hasnawi, Zainab Wanas Khadir (Al-Adab Journal, 2020)
The research dealt with the importance of the topographical side of the fold of Surdash during the variation of its manifestations in terms of degree of slope, inclination and extent of response of rocks to demolishing and structural geomorphic processes and their associated geomorphology, because the topography and its characteristic have a direct influence on the nature of geomorphological processes, which is the geomorphological risks in some parts of the region affecting investments and their type In the province of Sulaymaniyah, pre-studies should be conducted for it.